2019
DOI: 10.2147/ijn.s193170
|View full text |Cite
|
Sign up to set email alerts
|

<p>pH-sensitive doxorubicin-loaded polymeric nanocomplex based on &beta;-cyclodextrin for liver cancer-targeted therapy</p>

Abstract: Background: Doxorubicin (DOX) is one of the most effective treatments for hepatocellular carcinoma (HCC), but is restricted by its poor pharmacokinetics. Herein, we exploited efficient targeted drug delivery systems and they have been found to be a worthy strategy for liver cancer therapy. Materials and methods: We investigated polymeric nanoparticles which were synthesized based on host-guest interaction between β-cyclodextrin and benzimidazole. The properties of nanoparticles with regard to size/shape, encap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…The results are in accordance with the observation of Yang et al, which indicated that an acidic environment could accelerate the breakdown of self-assemblies, further giving rise to faster release of the drugs. 40 In the study carried out by Tang et al, the cellular uptake and cellular internalization mechanisms of nanoparticles in HeLa (high expression of FA receptor) cells were quantitatively detected by the fluorescence method. 41 In the FA receptor-overexpressing HeLa cells, the internalization of FA-decorated nanoparticles was significantly more efficient than undecorated ones due to FA receptormediated endocytosis and cellular macropinocytosis involved in the cellular internalizations of nanoparticles in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in accordance with the observation of Yang et al, which indicated that an acidic environment could accelerate the breakdown of self-assemblies, further giving rise to faster release of the drugs. 40 In the study carried out by Tang et al, the cellular uptake and cellular internalization mechanisms of nanoparticles in HeLa (high expression of FA receptor) cells were quantitatively detected by the fluorescence method. 41 In the FA receptor-overexpressing HeLa cells, the internalization of FA-decorated nanoparticles was significantly more efficient than undecorated ones due to FA receptormediated endocytosis and cellular macropinocytosis involved in the cellular internalizations of nanoparticles in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery systems (DDSs) constructed by nano carriers have attracted tremendous attention due to their better biocompatibiliy and lower side effects over the traditional naked drugs, which are considered to be one of the most active and promising treatment for cancer in future clinical applications (Zhou et al, 2017a;Rawal and Patel, 2019;Yang et al, 2019;Zhang et al, 2019a). Therefore, designing smart drug delivery systems with high drug loading efficiency and drug controlled-release in tumor microenvironment have been a hot topic (Gao et al, 2019;Xiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin (DOX) is one of the most effective treatments in many cancer types, with restrictions due to its pharmacokinetics 185 . To overcome limitations of classical chemotherapy and toxicity associated with DOX, different strategies are reported as alternatives.…”
Section: Application Of Ph‐responsive Polymersmentioning
confidence: 99%